The effectiveness of wound care education on wound healing in post caesarean section mothers - Irisanna Tambunan; Diana Ulfah; Renanda Nurul Azizah; Inez Komala Fitri (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Caesarean section (CS) is a common surgical procedure associated with postoperative wound complications if wound care is not optimally managed. Patient education plays a crucial role in improving mothers’ knowledge and supporting postoperative wound management, Purpose:  This study aimed to analyze the effectiveness of wound care education on knowledge level and wound healing outcomes among post-caesarean section mothers, Method: A quasi-experimental study with a non-equivalent control group pretest–posttest design was conducted. Thirty post-CS mothers were recruited using purposive sampling and divided into intervention and control groups. The intervention group received structured wound care education through leaflets and counseling, while the control group received standard education. Data were collected using a knowledge questionnaire and wound assessment (REEDA score). Data analysis was performed using the Wilcoxon Signed Rank Test, Results: The results showed a significant improvement in knowledge levels among mothers in the intervention group after receiving wound care education. However, no significant difference in wound healing outcomes was found between the intervention and control groups at the posttest, as all participants demonstrated good wound healing conditions, Conclusion: Wound care education effectively improves knowledge among post-caesarean section mothers but does not significantly affect short-term wound healing outcomes. Integrating structured wound care education into routine nursing care is recommended to support self-care and prevent postoperative complications.